2011
DOI: 10.1016/j.memsci.2011.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Membrane life estimation in full-scale immersed membrane bioreactors

Abstract: Limited quantitative available information exists regarding the robustness of membranes used in immersed membrane bioreactor (iMBR) applications, and no information on the relative contribution of the two main membrane failure modes of permeability and integrity loss. Such information is crucial given the significance of membrane replacement costs to the viability and sustainability of iMBRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…However, the volume flow and, hence, the required membrane area in 3a is still bigger than in 2a. [57] (the price reduces by 50% after three years of system operation); b 13 Pence/KWh (average UK electricity charge from 2012) [58]; c based on CombiBloc (Pump type 40-250) centrifuge pump performance data [50] and assumes 12 hours of pump operation per day; d adopted form Nolde [48] and Freidler and Hadari [49] for MBR and from Dillon [59] and leading UK CW companies; e includes the cost for replacing the pumps every 10 years and filters every five years, plus considering 2% of capital costs per year for general repair costs for other distribution system [60,61]; f in scenarios with MBR (2a and 3a), membrane modules (three MBR modules for Scenarios 2a and five MBR modules for Scenario 3a) were replaced every two years [57]-there is no decisive criterion that triggers end of membrane life [62], and two years (730 days) is not inappropriate based on maintaining at least a 98% threshold from the original manufacturers permeability rating [63]. (N.B.…”
Section: Expenses: Capex and Opexmentioning
confidence: 99%
“…However, the volume flow and, hence, the required membrane area in 3a is still bigger than in 2a. [57] (the price reduces by 50% after three years of system operation); b 13 Pence/KWh (average UK electricity charge from 2012) [58]; c based on CombiBloc (Pump type 40-250) centrifuge pump performance data [50] and assumes 12 hours of pump operation per day; d adopted form Nolde [48] and Freidler and Hadari [49] for MBR and from Dillon [59] and leading UK CW companies; e includes the cost for replacing the pumps every 10 years and filters every five years, plus considering 2% of capital costs per year for general repair costs for other distribution system [60,61]; f in scenarios with MBR (2a and 3a), membrane modules (three MBR modules for Scenarios 2a and five MBR modules for Scenario 3a) were replaced every two years [57]-there is no decisive criterion that triggers end of membrane life [62], and two years (730 days) is not inappropriate based on maintaining at least a 98% threshold from the original manufacturers permeability rating [63]. (N.B.…”
Section: Expenses: Capex and Opexmentioning
confidence: 99%
“…For backflushing, the key parameters in the design of physical cleaning have been identified as frequency, duration, the ratio between these two parameters and its intensity (Le-Clech et al, 2006), and the same key parameters are expected for relaxation (with the exception of intensity). However, there is a knowledge gap in the inter-relationships between those parameters and the imposed permeate flux, especially when comparing both methods to obtain the same water productivity (Wu et al, 2008 Ayala et al, 2011). However, at the moment, the optimization of chemical cleaning protocols is far from being fully resolved.…”
Section: Advantages and Challengesmentioning
confidence: 99%
“…However, analysis of the oldest plants evidence that membrane life can reach, or even exceed, 10 years (Verrech et al, 2010). Recently, Ayala et al (2011) has reported the effect of operating parameters on the permeability and integrity of cartridges taken from full-scale MBRs. Regarding permeability, a correlation of permeability loss and operation time was found, indicating that the membrane permeability reaches non-operative value after seven years of operation.…”
Section: Membrane Lifementioning
confidence: 99%
“…The mechanical failure was reported as a dominant factor to replace membranes (flat sheets in this specific case) [1]. In Schilde, a reduced capability to stand high TMPs was observed.…”
Section: T Life Concept Based On Membranes Mechanical Resistancementioning
confidence: 71%